Ovarian Reserve Tests: The Use in Daily Clinical Practice - Nusratuddin Abdullah (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To evaluate the significance of conducting ovarian reserve testing and decide when to order this testing in the clinical setting. And also to give individualized counseling to patients regarding the prognosis of infertility treatment based on their ovarian reserve tests, such as: basal antral follicle count, basal ovarian volume, ovarian stromal blood flow, ovarian biopsy, basal serum Follicle Stimulating Hormone (FSH), basal serum estradiol, basal serum inhibin B, basal anti-Mullerian hormone serum. Clomphine Citrate Challenge Test (CCCT), GnRH Agonist Stimulation Test (GA ST), and Exogenous FSH Ovarian Reserve Test (EFORT). Method: Literature study on published studies about the methods of ovarian reserve testing. Conclusion: Ovarian reserve is an important key in initial assessment of the infertile patients and as a predictor of the success of infertility treatment. Currently, there is no single test which is highly reliable for assessing ovarian reserve. AMH serum may be a future hope and suggested as the best biomarker. [Indones J Obstet Gynecol 2011; 35-4:235-40] Keywords: ovarian reserve test